Future insights of pharmacological prevention for AKI post cardiopulmonary bypass surgery (based on PK/PD approach) - Dias Permeisari (Frontiers Media S.A., 2022)
The incidence of acute kidney injury (AKI) post-cardiopulmonary bypass (CPB) can cause an increase in the rate of renal replacement therapy (RRT) and mortality rate. Compared to brain and liver damage post-CPB, AKI has the highest incidence of 83%. Based on this phenomenon, various efforts have been made to reduce the incidence of AKI post-CPB, both pharmacologically and non-pharmacologically interventions. The purpose of this review is to emphasize several renal protector agents which under optimal conditions can provide significant benefits in reducing the incidence of AKI post-CPB. This article was obtained by conducting a study on several kinds of literature, including the original article, RCT study, systematic review and meta-analysis, and other review articles. There are five renal protector agents that are the focus of this article, those are fenoldopam which effectively works to prevent the incidence of AKI post-CPB, while furosemide has shown satisfactory results in patients with decreased renal function when administered in the Renal Guard (RG) system, mannitol, and nitric oxide, both of these can also effectively reduce the incidence of AKI post‐CPB by controlling its blood concentration and timing of administration, and another form of N-Acetylcysteine, namely N‐Acetylcysteine amide has better activity as a renoprotective agent than N‐Acetylcysteine itself. The benefits of these agents can be obtained by developing devices that can control drug levels in the blood and create optimal conditions for drugs during the use of a CPB machine.